Use of E-resources by Users of Yuvaraja College: University of Mysore - A Study - Sarasvathy, P.; Bhyrappa, M.; Giddaiah, D.; Manjunath, M.; Harisha, R. (Journal of Information and Knowledge, 2014)
The study aimed at finding the use of e-resources by the research scholars and faculty including guest faculty in the University of Mysore. 110 questionnaires distributed randomly and 82 filled-in questionnaires were received back with a moderate response rate 90%. The results show that e-resources are most important for scientific communication and research work. The library should also conduct brain storming workshop to help adapt to the new technology that often gets outdated.